Market segmentation analysis to find out products and services that suit customer needs using the python KMEANS clustering method (Case study: Superindo Tambun Area, Bekasi) - Praditya , Rizqy Gumilar; Sembodo, Giri; Heikal, Jerry (LPPM Universitas Pahlawan Tuanku Tambusai, 2024)
This study analyzes market segmentation of 1000 Superindo consumers in Tambun, Bekasi, using K-Means Clustering with Python 3.10. Variables included age, gender, occupation, purchase amount, product type, and discounts. Three main segments were identified: